Characterization, antibacterial and biological activities of phenolic fraction of argentinean red wines - Stivala, Maria Gilda; Villecco, Margarita Beatriz; Fanzone, Martín Leandro; Jofre, Viviana Patricia; Rodriguez Vaquero, Maria Jose; Aredes Fernández, Pedro Adrián (Bentham Open, 2019)
For the first time, the qualitative and quantitative characterization of phenolic compounds of lower molecular weight fraction (LMF) were evaluated in commercial Cabernet Sauvignon (CS) and Tannat (T) wines varieties produced in Cafayate, Argentine. The antimicrobial activity against Pediococcus pentosaceus 12p, spoilage wine bacteria as well as the “in vitro” antioxidant and antihypertensive activities were also evaluated. The composition of LMF obtained by liquidliquid extraction with ethyl acetate, determined by HPLC-DAD, showed a total content of phenolic compounds of 229.4 and 311.1 mg L-1 for CS and T wines respectively. Synthetic like-wine media (SWM), pH 4.5 supplemented with LMF at identical concentration of the wine (1X), four (4X) and eight times concentrated (8X), was inoculated with P. pentosaceus 12p at 107CFU mL-1. Samples were collected at the beginning and final incubation time to determine cell viability in MRS-agar medium and the damage of the cell membrane integrity by electron microscopy observation. In the presence of LMF at 1X concentration, both fractions diminish growth parameters without cellular damage. In the presence of LMF of CS and T wine varieties four and eight times concentrated, cellular death of the microorganism as well as plasmatic membrane disruption was observed. The LMF of both wines analyzed in this study have high antioxidant, radical scavenging and antihypertensive activity. The use of phenolic compounds as potential antimicrobial agents could be an effective additive to controll wine spoilage bacteria, adding on wines beneficial properties to human health.